Dust coma of comet C/2009 P1 (Garradd) by imaging polarimetry. (26th April 2013) - Hadamcik, E.; Sen, A. K.; Levasseur‐Regourd, A. C.; Roy Choudhury, S.; Lasue, J.; Gupta, R.; Botet, R.
Abstract Comet C/2009 P1 (Garradd) was observed by imaging polarimetry for nearly 5 months from October 2011 to March 2012, over an intermediate phase angle range (28°–35°). Two months before perihelion and one month after, dust particles seem to be ejected all around the optocenter and jets extend to distances greater than 40, 000 km. An increase of activity is noticed in intensity and polarization after perihelion. Two months before perihelion and one month after, the dust emission seems to be all around the optocenter. Two and three months after perihelion the jets are mainly toward the solar direction with an extension of more than 20, 000 km projected on the sky. The values of the aperture polarization are comparable to those of other comets. On the polarization maps in October 2011 and January 2012 the higher polarization zones extend in large regions perpendicularly to the solar direction where jets are also observed. In February and March 2012, the polarization in the jets is larger in the solar direction than in the surrounding coma. By its activity visible on intensity images and polarization maps at large distances from the nucleus, comet Garradd probably belongs to the high‐Pmax class of comets.